Analysis of Independence Completing The Assignment in Entrepreneurship Learning Class IV Students at Sd Negeri 2 Waluyo - Fenti Retnoningrum; Rokhmaniyah Rokhmaniyah (Social, Humanities, and Educational Studies (SHEs): Conference Series, 2019)
In entrepreneurship learning, students are required to complete assignments independently with the intention of creating an independent, responsible, and good entrepreneurial generation. This study aims to describe the independence of students in completing assignments in the fourth grade entrepreneurship learning process at SDN 2 Waluyo. This research approach uses a qualitative approach and descriptive research type. The subjects of this study were students in class IV at SDN 2 Waluyo, totaling 28 students. Data collection was carried out using observation techniques, questionnaires, and classroom teacher interviews. The results of this study indicate that independence in the good category is self-confidence, being able to work alone, respecting time, and being responsible. While independence is in the sufficient category is to have the desire to compete to move forward and be able to make decisions.